Stolen Words : The Nazi Plunder of Jewish Books - Glickman, Mark, 1963- (Book collections on Project MUSE., 2016)
"How the largest Jewish book collection in the world--four to five million volumes--was looted by the Nazis and recovered by the Allied Forces"--